Review: The Effect of the Teaching Game For Understanding Model on Cognitive Ability - Rinaldo Rinaldo; Beltasar Tarigan; Tite Juliantine (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Physical education has an important role in helping students develop quality skills. The Teaching Games for Understanding (TGFU) approach is a learning model that focuses on developing abilities through the form of basic playing concepts. TGFU is considered to have an influence in improving learning skills, especially in the domain of cognitive abilities such as decision making. This study describes the effectsthe TGFU model of cognitive abilities. The design of this writing is study literature review. The results of several studies indicate an increase in cognitive abilities in students who apply the TGFU learning model in the implementation of sports and games.